Pengembangan E-Modul Fikih dalam Pembelajaran Fikih untuk Madrasah Tsanawiyah di Medan - Sri Wahyuni Harahap; Mardianto Mardianto; Salminawati Salminawati (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to develop a Fiqh E-Module that is in accordance with the curriculum and learning needs in class VII MTs Irsyadul Islamiyah. This research uses research and development methods. The development model used is the ADDIE (analysis-design-development-implementation-evaluation) development model. Several relevant data collection techniques to support this research are observation, questionnaires, interviews, tests and documentation. The data collected in this research includes qualitative data and quantitative data. Qualitative data comes from criticism, suggestions, input and comments from experts (validators) and Fiqh teachers, while quantitative data is in the form of assessment sheets given to validators to assess the Fiqh e-module being developed, questionnaires to find out students' responses to the e-module. The jurisprudence used and the test results are pre-test and post-test scores from learning Jurisprudence using the Jurisprudence e-module and before using the Jurisprudence e-module. The population in this study were class VII MTs students. The researcher took research samples from class VII A students at MTs Irsyadul Islamiyah Tanjung Medan Labuhanbatu Selatan, totaling 40 people. The sampling technique is nonprobability sampling technique, the technique used is purposive sampling. Qualitative data will be analyzed using descriptive analysis. Quantitative data was analyzed by calculating the percentage of answers to each question item given to respondents. The results of data analysis use data interpretation criteria. The results of this research were validated by two experts, the first being a material expert who obtained 98% results, and a media expert and technology expert who obtained 78% results in the very valid category. After that, it was tested on students by getting a pre-test score of 47.8, then getting a post-test score of 84.8 in the very feasible category, and the practicality level obtained a score of 89.8% in the very practical category.